Internal customers' satisfaction towards service quality management at ecotourism destinations - Lee, Wen Yuan (Universiti Malaysia Sarawak, UNIMAS, 2011)
In brief, this study is aim to measure the internal customers’ satisfaction towards service quality management at ecotourism destinations. There are four service quality management dimensions been used as the indicator in measure the internal customers’ satisfaction. 120 sets of questionnaires were distributed to the employees in different ecotourism destinations to collect their respond. Furthermore, the collected data in this study were analyzed by using descriptive statistic and statistical analysis. There are two new dimensions been found in this study which consists of organization culture and training evaluation. The finding of this study found that training opportunities and organization culture are partially significant to internal customers’ satisfaction. Also, the study found that the service quality management does not fully support the internal customer satisfaction because of the regardless of the management for encouraging people to be creative and innovative. There are some limitations in this study that faced by the researcher, they are; small of scope of the study, respondents biases in answering questionnaire, limited variables in measured the study, and the unwillingness of the management of ecotourism destinations to give cooperation.